Pengaruh Latihan TRX Exercise Jump Squat Terhadap Power Otot Tungkai - Ridha Oktaviana; Nana Sutisna; Ucu Abdul Ropi; Tony Hartono (Jurnal Keolahragaan, 2023)
This study aims to examine the effect of TRX jump squat training on increasing leg muscle power in extracurricular bolavoli students at SMAN 1 Sukadana. The research method used was an experiment with a one-group pretest-posttest design. The population in this study were all members of the extracurricular bolavoli SMAN 1 Sukadana, with a sample of 20 people selected using purposive sampling technique. The instrument used to measure leg muscle power is the vertical jump test. Data were analyzed using the Paired Sample T-Test test. The results showed a significance value (p) of 0.000, which is smaller than 0.05 (α=0.05). This indicates that there is a significant effect of TRX Jump Squat training on increasing leg muscle power. Thus, TRX Jump Squat training can be recommended as one of the training methods to increase the leg muscle power of bolavoli athletes.